MARITAL VIOLENCE CONTEXT AFTER THE MARIA DA PENHA LAW: A GROUNDED THEORY STUDY - Jordana Brock Carneiro; Nadirlene Pereira Gomes; Luana Moura Campos; Nildete Pereira Gomes; Kamylla Santos da Cunha; Ionara da Rocha Virgens; Alacoque Lorenzini Erdmann (Universidade Federal do Paraná, 2019)
Objective: To analyze the context of marital violence experienced by women in legal proceedings. Methodology: This is a qualitative study based on the grounded theory, conducted with 29 women in legal proceedings for marital violence and nine professionals who work at two Courts for Peace at Home in Bahia, Brazil. Data collection was performed from January to May 2015. Results: Despite the Maria da Penha Law, the study shows that marital relationships of women are permeated by physical, sexual, psychological, moral and property abuse, with some of them being sent away from home.Conclusion: Marital violence contexts appear in different ways, which can be identified by health professionals, allowing women's care actions to address the problem